Способ прогнозирования износостойкости твердосплавных режущих инструментов - Нестеренко В. П. Владимир Петрович; Тюрин Ю. И. Юрий Иванович; Арефьев К. П. Константин Петрович; Матвеенко В. И. Василий Иванович; Лычагин Д. В. Дмитрий Васильевич
опубл. 20.10.09